Impact of sol mixture composition on organosilica coatings formation on glass substrates - A. O. Mosendz; M. F. Zui (Хімія, фізика та технологія поверхні, 2025)
In this study, hybrid organosilica coatings on glass substrates were synthesized using mixtures of the active polymer OH-terminated PDMS and one or more precursors, namely methyltrimethoxysilane bis(3-trimethoxysilylpropyl) amine, phenyltrimethoxysilane, cyanopropyltrimethoxysilane, aminopropyltriethoxysilane in the presence of modifiers (polyethylene glycol, organic solvents) and trifluoroacetic acid catalyst. The aim of this work was to obtain new sorption materials for the extraction of nonpolar and semi-polar analytes, for example, carbonyl compounds in the form of PFBHA derivatives, azo dyes, phthalates, and others, and to purify samples with a complex matrix for further gas chromatographic analysis. The advantages of the obtained sorption coatings are the effective separation of micro quantities of target compounds of nonpolar and semi-polar nature from polar compounds present in aqueous samples in rather high concentrations.